2007
DOI: 10.1177/1090198106290622
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Community Action Against Asthma: A Community Health Worker Intervention to Improve Children's Asthma-Related Health by Reducing Household Environmental Triggers for Asthma

Abstract: This article describes the evaluation of a community-based participatory research (CBPR) community health worker (CHW) intervention to improve children's asthma-related health by reducing household environmental triggers for asthma. After randomization to an intervention or control group, 298 households in Detroit, Michigan, with a child, aged 7 to 11, with persistent asthma symptoms participated. The intervention was effective in increasing some of the measures of lung function (daily nadir Forced Expiratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
104
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(108 citation statements)
references
References 33 publications
3
104
1
Order By: Relevance
“…Two of four RCTs demonstrated a significant decrease relative to control, 40,53 and two showed no significant decrease relative to control. 54,55 Of the four pre-post studies measuring this outcome, three demonstrated a statistically significant decrease, 41,44,45 and one showed a non-significant increase.…”
Section: Emergency Department Visitsmentioning
confidence: 86%
“…Two of four RCTs demonstrated a significant decrease relative to control, 40,53 and two showed no significant decrease relative to control. 54,55 Of the four pre-post studies measuring this outcome, three demonstrated a statistically significant decrease, 41,44,45 and one showed a non-significant increase.…”
Section: Emergency Department Visitsmentioning
confidence: 86%
“…Such home visits reduce exposure to triggers, decrease symptoms and urgent healthcare use, and increase quality of life. 7,[53][54][55][56][57][58][59][60][61][62] Visitors assess home environmental conditions, tailor education on how to eliminate triggers to the client's sensitization status and exposures found in the home, provide trigger reduction resources (eg, vacuums, cleaning supplies, bedding encasements, and referral to smoking cessation), help with cockroach and rodent integrated pest management, make minor repairs, and provide social support. Importantly, visitors build trusting relationships with clients, thus enhancing their effectiveness in motivating behavior changes.…”
Section: Interventions To Reduce Exposure To Triggersmentioning
confidence: 99%
“…Important questions regarding home visits remain unanswered regarding the relative merits of different types of home visitors (programs have employed various types of visitors, such as CHWs, sanitarians, nurses, and doctors, 57 with current evidence showing no difference in outcomes 53,55,58 ), the most cost-effective intensity and duration of the intervention, the possibility of substituting telephone contact for some of the follow-up visits, the durability of intervention effect, and the role of home visits in higherincome and more privileged populations generally not included in existing studies. Further research to address these issues is warranted.…”
Section: Where To Go From Herementioning
confidence: 99%
“…Examples of CHW roles include providing health education, performing patient navigation, and directly delivering medical services, such as immunizations 26 . CHW programs have targeted many diseases-diabetes 27-30 , cancer [31][32][33][34][35] , cardiovascular disease [36][37][38][39] , and asthma [40][41][42][43][44] in addition to focusing on general health promotion 45 and maternal/child health [46][47][48] .…”
Section: Introductionmentioning
confidence: 99%